Incidencia de Hongos Asociados al Arroz Rojo en el Sur del Paraguay (Journal on studies and research of academic knowledge, 2018)
Weeds reduce rice yields and quality through direct competition and on crop health since some of the associated species are presented as alternate hosts of diseases that constitute a source of early infection for the crop. 150 samples of diseased parts (leaves, spikes, grain) of weedy red rice (Oryza sativa L.) were collected at random from march 2015 to april 2016 from different rice-growing areas. The objective of the research was to determine the incidence of fungal species associated with weedy rice in the south region of the country. The research were carried out in the Microbiology laboratory of the Faculty of Science and Technology of the National University of Itapúa (UNI) Encarnación. The technique used was the filter paper method. The identification of the fungus was carried out based on structures of the fungus (conidia) observed at the stereoscope and optical microscope. Specialized keys were used as tools to identify the genus and species. The fungal species identified on weedy rice were Bipolaris oryzae, Alternaria padwickii, Curvularia lunata sp., Fusarium sp., Alternaria sp. and Pyricularia sp. The fungi B .oryzae (82%) and Curvularia sp. (70%) showed the highest incidence (82% and 70%) respectively. All identified fungi are causal agents of diseases in rice crop.
Keywords: Oryza sativa; weedy rice; fungus; microorganisms